Competição e digitalização: a expansão dos serviços culturais-digitais – os casos da Netflix, Disney e Apple - Elder Patrick Maia Alves (Ciências Sociais Unisinos)
This work investigates the process of competition between some of the most important technology companies in the world, which created business models aimed at the culturaldigital services market - series, movies, games, music, books and animation. It is a process of global scope and great economic, technological and creative impact, which has been refashioning the cultural markets through the intense process of digitalization and corporate action. To analyze these aspects, two methodological and analytical strategies were adopted simultaneously along the text. The first one sought to use the concepts of digitalization of the symbolic and cultural-digital capitalism, both of which are woven into other works and research that combine a broader research agenda, whose efforts are engaged in the realization of an economic sociology of cultural markets. The second was to explore the latest economic decisions and commercial and creative strategies adopted by the Netflix, Disney and Apple companies, as well as to update data on the expansion of consumption of digital artistic-cultural content, especially in Brazil.